SCREENING OF CABBAGE VARIETIES FOR RESISTANCE TO PLUTELLA XYLOSTELLA (LINN.) - SHUKLA, ABHISHEK; KUMAR, ASHOK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
Thirteen cabbage varieties were evaluated in the field for their resistance to diamond back moth (DBM), Plutella xylostella (Linn.) in rabi 2001-02. Based on DBM infestation and mean yield cabbage varieties Madhavi, Krishna, Stonehead and Fieldman were found highly resistant, while MCB-1, Golden acre, Haragola and Deepa-270 exhibited as moderately resistant. The varieties SPCS-3, BC-79, NS-22, NS-25 and Quiesto were found least resistant to DBM attack. On the basis of their resistance, the cabbage varieties were arranged in the following order: Madhavi > Krishna > Stonehead > Fieldman >MCB-1 > Golden acre > Haragola > Deep-270 > SPCS-3 > BC-79 > NS-22 > NS-25 > Quiesto.